Cyclic Adenosine Monophosphate Regulation of Ion Transport in Porcine Vocal Fold Mucosae - Sivasankar, Mahalakshmi (2008)
OBJECTIVES/HYPOTHESIS: Cyclic adenosine monophosphate (cAMP) is an important biological molecule that regulates ion transport and inflammatory responses in epithelial tissue. The present study examined whether the adenylyl cyclase activator, forskolin, would increase cAMP concentration in porcine vocal fold mucosa and whether the effects of increased cAMP would be manifested as a functional increase in transepithelial ion transport. Additionally, changes in cAMP concentrations following exposure to an inflammatory mediator, tumor necrosis factor-α (TNFα) were investigated. STUDY DESIGN: In vitro experimental design with matched treatment and control groups. METHODS: Porcine vocal fold mucosae (N = 30) and tracheal mucosae (N = 20) were exposed to forskolin, TNFα, or vehicle (dimethyl sulfoxide) treatment. cAMP concentrations were determined with enzyme-linked immunosorbent assay. Ion transport was measured using electrophysiological techniques. RESULTS: Thirty minute exposure to forskolin significantly increased cAMP concentration and ion transport in porcine vocal fold and tracheal mucosae. However, 30-minute and 2-hour exposure to TNFα did not significantly alter cAMP concentration. CONCLUSIONS: We demonstrate that forskolin-sensitive adenylyl cyclase is present in vocal fold mucosa, and further, that the product, cAMP increases vocal fold ion transport. The results presented here contribute to our understanding of the intracellular mechanisms underlying vocal fold ion transport. As ion transport is important for maintaining superficial vocal fold hydration, data demonstrating forskolin-stimulated ion transport in vocal fold mucosa suggest opportunities for developing pharmacological treatments that increase surface hydration.